For Sama [videorecording (DVD)] - Al-Kateab, Waad (PBS DVD video., 2019)
The Frontline film is both an intimate and epic journey into the female experience of war. A love letter from a young mother to her daughter, the film tells the story of Waad al-Kateab's life through five years of the uprising in Aleppo, Syria as she falls in love, gets married and gives birth to Sama; all while Waad films the cataclysmic conflict raging around them.